The Charmed readers print media's reportage of the Visiting Forces Agreement and its possible influence in forming the opinion of the people, based on the sentiments in the letters and opinion sections of major Philippine newspapers : a relational study - Barcelona, Lyn A.
In a world that can be overwhelming with simultaneous significant and insignificant events, print media when deciding what to publish, consciously or unconsciously, takes the role of a gatekeeper of information flow. It not only gives the people its selected information, but also weighs for the people what they should consider important by reporting it and omitting from the report or paper what it deems is irrelevant. It has the capability to decide for the public what the people should know of, and be informed about, as explained by McCombs and Shaw's Agenda Setting Function and Media Gatekeeping Concept of McQuail and Windahl. In the Philippines, where press freedom is exercised at its dullest, the handling and treatment of important and sensitive issues and its influence to the formation of opinion was scrutinized in this study. And VFA being one of the most debated events in the country during that time is the event that this study looked into. The event of which almost everyone has an opinion about it and every newspaper contained news regarding it. Utilizing content analysis, the findings showed that people think and evaluate matters as the media tells them to. During February 1998, the media was full of May 1998 Presidential Election and the Cebu Pacific Plane Crash articles, the signing of VFA between the United States of America and the Republic of the Philippines was put in the sideline. But come August 1998, when the Malacañang Palace was asking the Senate for an early approval, the phenomenon reached its peak. The media thought that they had the responsibility of telling the people of what was happening especially when it was about the international relationship of the Philippines with other countries, more particularly the United States, one of the most powerful and influential nation in the world. Soon every newspaper was writing about the VFA. The agreement was hugging the headlines and a large portion of the front page. Given this exposure, people started to notice the issue, talked and debated over it and in time aired their opinion in the Letters to the Editor section of the newspapers. Some readers even got a more active role in voicing their beliefs of the issue. They took part in mobilizations and rallied for their stand. It got so big that it became an issue of public concern. Print media chooses which news to report and how to report it on paper. It gives hints on how the readers should view the issue, thus, influencing the attitude and opinion of the readers towards it.